Optimal Cooperative Taxation in the Global Economy - Chari, V. V.; Nicolini, Juan Pablo; Teles, Pedro (Journal of Political Economy, 2023)
How should countries cooperate in setting fiscal and trade policies when government expenditures must be financed with distorting taxes? We show that even if countries cannot make explicit transfers to each other, every point on the Pareto frontier is production efficient, so that international trade and capital flows should be effectively free. Trade agreements must be supplemented with fiscal policy agreements. Residence-based income tax systems have advantages over source-based systems. Taxing all household asset income at a country-specific uniform rate and setting the corporate income tax to zero yield efficient outcomes. Value-added taxes should be adjusted at the border.